Comparison of different methods for determination of Pt surface site concentrations for supported Pt electrocatalysts - Punyawudho K. (2014)
Platinum surface atom (or site) concentrations for a series of commercially available 10, 20, and 40 wt% Pt/C electrocatalysts have been determined using X-ray diffraction (XRD), high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), selective chemisorption, and cyclic voltammetry (CV) methods. Each method of analysis was repeated for a sufficient number of times to determine reproducibility and standard deviation limits. Comparison of the results shows that XRD and STEM methods give Pt surface site concentrations much higher than for chemisorption analysis due to assumptions regarding Pt particle shapes and particle size distributions. The results from CV analysis agree reasonably well with those from chemisorption if the sample amounts and methods of sample deposition preceding CV analysis can be well-controlled and there is no loss of surface exposure by the Nafion over-layer. Because both chemisorption and CV analyses more directly measure actual site concentrations with fewer assumptions, these methods should be considered superior to XRD and STEM analyses. Further, since chemisorption uses substantially larger sample sizes (up to 0.25 g) compared to CV (<0.01 g), reliability of chemisorption data is much more reliable and should be considered as the metric for surface Pt site determination. © 2010 Elsevier Ltd. All rights reserved.